Implementasi Pembelajaran Kitab Ikhtishor Nahwuiyah Dalam Meningkatkan Kemampuan Baca Kitab Kuning Santri Putra Pondok Pesantren Hidayatul Mubtadi'in Jati Agung Lampung Selatan - Eka Putra Wicaksono; Sarpendi Sarpendi; Zulfa Rohmawati (Penerbit Widina, Widina Media Utama, 2026)
This study aims to explore the effectiveness of implementing the Ikhtishor Nahwuiyah (Islamic Text) learning method in improving the reading skills of male students at the Hidayatul Mubtadi'in Islamic Boarding School in Jati Agung, South Lampung. This study demonstrates that the systematic, structured, and participatory implementation of the Ikhtishor Nahwuiyah learning method significantly contributes to improving the reading competence of male students at the Hidayatul Mubtadi'in Islamic Boarding School in Jati Agung. This learning method improves understanding of nahwu rules, practical reading skills, as well as fluency and accuracy of texts. The approach, which combines theory with hands-on practice, intensive training, social interaction, and guidance from senior ustadz (Islamic teachers), fosters motivation, discipline, and character development among students. These findings align with the principles of Constructivist Learning, Experiential Learning, and Self-Determination Theory, and confirm that this learning model effectively integrates classical Islamic boarding school traditions with a modern pedagogical approach for comprehensive mastery of the yellow book. This research uses a qualitative approach with a case study design to explore the effectiveness of learning the Ikhtishor Nahwuiyah book in improving the yellow book reading skills of male students at the Hidayatul Mubtadi'in Islamic Boarding School in Jati Agung, South Lampung. The research subjects included students, teachers, and boarding school administrators. Data were collected through participant observation, in-depth interviews, and documentation of learning materials. Analysis was conducted thematically using triangulation of sources, techniques, and theories. This method allows for an in-depth understanding of the learning process, social interactions, and strategies for mastering the rules of nahwu, while simultaneously evaluating the effectiveness of the yellow book reading practice.ABSTRAKPenelitian ini bertujuan untuk mengeksplorasi efektivitas implementasi pembelajaran kitab Ikhtishor Nahwuiyah dalam meningkatkan kemampuan membaca kitab kuning santri putra di Pondok Pesantren Hidayatul Mubtadi’in Jati Agung, Lampung Selatan. Penelitian ini menunjukkan bahwa implementasi pembelajaran kitab Ikhtishor Nahwuiyah secara sistematis, terstruktur, dan partisipatif memberikan kontribusi signifikan terhadap peningkatan kompetensi santri putra di Pondok Pesantren Hidayatul Mubtadi’in Jati Agung dalam membaca kitab kuning. Pembelajaran ini meningkatkan pemahaman kaidah nahwu, kemampuan membaca praktik, serta kefasihan dan akurasi teks. Pendekatan yang menggabungkan teori dengan praktik langsung, latihan intensif, interaksi sosial, dan bimbingan ustadz senior mendorong motivasi, kedisiplinan, dan pembentukan karakter santri. Temuan ini sejalan dengan prinsip Constructivist Learning, Experiential Learning, dan Self-Determination Theory, serta menegaskan bahwa model pembelajaran ini efektif mengintegrasikan tradisi pesantren klasik dengan pendekatan pedagogi modern untuk penguasaan kitab kuning secara menyeluruh. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus untuk mengeksplorasi efektivitas pembelajaran kitab Ikhtishor Nahwuiyah dalam meningkatkan kemampuan membaca kitab kuning santri putra di Pondok Pesantren Hidayatul Mubtadi’in Jati Agung, Lampung Selatan. Subjek penelitian meliputi santri, pengajar, dan pengurus pesantren. Data dikumpulkan melalui observasi partisipatif, wawancara mendalam, dan dokumentasi materi pembelajaran. Analisis dilakukan secara tematik dengan triangulasi sumber, teknik, dan teori. Metode ini memungkinkan pemahaman mendalam tentang proses pembelajaran, interaksi sosial, dan strategi penguasaan kaidah nahwu, sekaligus mengevaluasi efektivitas praktik membaca kitab kuning.